2021
DOI: 10.3389/fped.2021.674156
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in Pediatric Heart Failure and Heart Transplant

Abstract: Survival of pediatric patients with heart failure has improved due to medical and surgical advances over the past decades. The complexity of pediatric heart transplant patients has increased as medical and surgical management for patients with congenital heart disease continues to improve. Quality of life in patients with heart failure and transplant might be affected by the impact on functional status that heart failure, heart failure complications or treatment might have. Functional areas affected might be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Ubeda Tikkanen et al34 reviewed the literature on rehabilitation in pediatric patients with heart failure and patients with heart transplant and highlighted the benefits of exercise training for improving functional status and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubeda Tikkanen et al34 reviewed the literature on rehabilitation in pediatric patients with heart failure and patients with heart transplant and highlighted the benefits of exercise training for improving functional status and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the recipients of HTx had generally favorable cardiovascular health scores that were similar to the general population, but they also found that cardiovascular health was poorer with older age and non-Caucasian race/ethnicity among the recipients of HTx. 33 Ubeda Tikkanen et al 34 reviewed the literature on rehabilitation in pediatric patients with heart failure and patients with heart transplant and highlighted the benefits of exercise training for improving functional status and quality of life.…”
Section: Younger Recipients Of Htx Versus Older Recipients Of Htxmentioning
confidence: 99%
“…Much research is needed to elucidate frailty and sarcopenia diagnostic standards and treatment in children with end‐stage organ disease to improve morbidity, mortality, and patient‐centered outcomes such as life participation. Exercise and physical preprogram/rehabilitation programs have been identified as an effective treatment, especially in the setting of sarcopenia and frailty 128–132 . Multidisciplinary care and research is necessary for the advancement of care in the pediatric end‐stage organ disease and transplant populations.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise and physical preprogram/rehabilitation programs have been identified as an effective treatment, especially in the setting of sarcopenia and frailty. [128][129][130][131][132] Multidisciplinary care and research is necessary for the advancement of care in the pediatric end-stage organ disease and transplant populations. This review serves to provide enough background and critical evaluation for pediatric nutrition clinicians to implement diagnostic and measurement techniques described here and in the future to aid in their assessments of malnutrition, sarcopenia, and frailty despite the limited consensus and research available.…”
Section: Implications and Future Directionsmentioning
confidence: 99%